Cross-Sectional Study in a Large Cohort of Chinese Patients With GJB1 Gene Mutations - Liu, Xiaoxuan; Duan, Xiaohui; Zhang, Yingshuang; Sun, Aping; Fan, Dongsheng (Frontiers in Neurology, 2020)
Charcot-Marie-Tooth disease is a clinically and genetically heterogenous group of inherited neuropathies. The GJB1 gene is the pathogenic gene of CMTX1. In this study, we screened a cohort of 465 unrelated Chinese CMT patients from year 2007 to 2019 and 650 controls by direct Sanger Sequencing in GJB1 gene or targeted Next-Generation Sequencing (NGS) or Whole-Exome Sequencing (WES). A bidirectional Sanger sequencing would be performed on the 600 bases in the upstream promotor region and 30 bases in the 3’ untranslated region (UTR), if no mutation was found in the coding region of GJB1 of the patient. According to the results, 24 missense mutations, 4 nonsense mutation, 1 entire deletion, 1 intronic mutation and 4 frameshift mutations in GJB1 were identified. Three of them were novel mutations (c.104 T>C, c.658-659 ins C, c.811 del G). Moreover, central nervous system involvement was observed in 5 patients carrying mutations of R15W, V95M, R142W, R164W, E186K, respectively. Our findings expand the mutational spectrum of GJB1 gene in CMT patients. We also explored the genotype-phenotype correlation according to the collected information in this study. NGS panels for detecting inherited neuropathy should cover the noncoding region of GJB1.